Kisah Kehancuran Tentara Bergajah dalam Surah Al-Fil Tinjauan Ilmu Epidemiologi - Harfin dan Limmatus Sauda (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
This research departs from the story of the destruction of Abrahah and his army in Al-Fi>l which is interpreted by some commentators as an event from an outbreak of disease. This meaning has given rise to polemics among commentators. In addition, the meaning of the disease is also stopped only to the exent of conjecture without being accompanied by complete information, especially on the side of scientific explanations. For this reason, the purpose of this study is to further examine the views of some commentators regarding the disease outbreak in the story of destruction of elephant army. The method used in this reseach is qualitative method with the type of library research. Furthermore, this study uses an epidemiologycal approach to further analyze the disease associated with the destruction of the elephant army. The result of this study revealed that the ababil birds is a reservoir animal that carries disease agents where the agent play an active role in creating a disease that can destroy elephant soldier in an instant. However, there has been No. discovery similar to the disease as describe in the story.